Systematics of the green lacewing tribe Ankylopterygini Navás, 1910 (Neuroptera: Chrysopidae: Chrysopinae) from China - Wu, Jingyu; Liu, Xingyue (Zootaxa, 2024)
A systematic revision of the taxonomy of the green lacewing tribe Ankylopterygini (Neuroptera: Chrysopidae: Chrysopinae) from China is present. Sixty-six species belonging to six genera are recorded and described. Keys to genera, subgenera and species are provided. A total of 201 COI barcodes (partial sequence of cytochrome c oxidase subunit I (COI)) from 49 species of the tribe are provided and used for molecular species delimitation. Nineta Navás, 1912 is treated as a subgenus of Tumeochrysa Needham, 1909. Two new generic synonyms are proposed: Tibetochrysa Yang, 1988, junior synonym of Retipenna Brooks, 1986; Sencera Navás, 1925, junior synonym of Ankylopteryx Brauer, 1864. Sixteen new species are described: Ankylopteryx hainanensis sp. nov., A. montipunctata sp. nov., A. stena sp. nov., Chrysopidia arcta sp. nov., C. macrosterna sp. nov., C. abdominata sp. nov., Tumeochrysa acuta sp. nov., T. breva sp. nov., T. biloba sp. nov., T. minina sp. nov., T. yangi sp. nov., Retipenna interrupta sp. nov., R. triphlebia sp. nov., Semachrysa pura sp. nov., Se. triloba sp. nov. and Signochrysa jianfenglingensis sp. nov. Twelve specific synonyms are proposed: Ankylopteryx yangi Ma, Yang & Liu, 2020, junior synonym of Ankylopteryx octopunctata candida (Fabricius, 1798), Chrysopidia yangi Yang & Lin, 1977, junior synonym of Chrysopidia junbesiana Hölzel, 1973; Chrysopidia fuscata Navás, 1914 and Chrysopidia tjederi Ma, 2022, junior synonyms of Chrysopidia regulata Navás, 1914; Tumeochrysa hui Yang, 1987, junior synonym of Tumeochrysa praeclara Hölzel, 1973; Tumeochrysa nyingchiana Yang, 1987, junior synonym of Tumeochrysa yunica Yang, 1986; Retipenna inordinata, Yang, 1997, junior synonym of Retipenna dasyphlebia (McLachlan, 1894); Retipenna chione (Banks, 1942 [1940]), junior synonym of Retipenna grahami (Banks, 1942 [1940]); Retipenna chaoi Yang & Yang, 1987, Retipenna guangdongana Yang & Yang, 1987 and Retipenna huai Yang & Yang, 1987, junior synonyms of Retipenna burmana Brooks, 1986; and Signochrysa hainanus (Yang & Yang, 1991), junior synonym of Signochrysa ornatissima (Nakahara, 1955). Eight new combinations are proposed: Retipenna phanera (Yang, 1987) comb. nov., R. sinica (Yang, 1988) comb. nov., Tumeochrysa abunda (Yang & Yang, 1989) comb. nov., T. dolichoptera (Navás, 1910) comb. nov., T. grandis (Navás, 1915) comb. nov., T. inpunctata (Reuter, 1894) comb. nov., T. shaanxiensis (Yang & Yang, 1989) comb. nov. and T. vittata (Wesmael, 1841) comb. nov. Ten species are newly recorded from China: Chrysopidia junbesiana Hölzel, 1973, C. nigrata Navás, 1910, C. ciliata (Wesmael, 1841), C. orientalis (Hölzel, 1973), Tumeochrysa inpunctata (Reuter, 1894), T. praeclara Hölzel, 1973, T. magnifica Hölzel, 1973, Retipenna burmana Brooks, 1986, R. variegata Brooks, 1986, and Semachrysa contorta Brooks, 1983. One species is transferred from Ankylopterygini to Chrysopini: Chrysopa yananica (Yang & Yang, 1989) comb. nov.